In Situ Testing Evaluation and Numerical Simulation of CFRP-Strengthened Reinforced Concrete Two-Way Slab with Initial Defect - Yepu Sheng; Yu Gong (Buildings)
Carbon fiber-reinforced polymer (CFRP) composites, renowned for their high strength-to-weight ratio, are increasingly utilized in the strengthening of structural components. The application of CFRP for strengthening concrete components notably improves the cracking moment and substantially elevates the ultimate load-bearing capacity. This study focuses on a reinforced concrete (RC) two-way slab with an initial defect, specifically an initial deflection. To avert deformations or damages that could break structural integrity during service, the slab was strengthened by adhering CFRP to its underside. An in situ multi-stage loading test was conducted to evaluate the load-bearing capacity of the CFRP-strengthened slab, and the findings revealed that the mid-span deflection of the two-way slab incrementally reached 1.64 mm after the loading stages, with no observable signs of concrete cracking, debonding, or tearing of the CFRP-strengthened slab. The failure modes indicated a transition from concrete compression damage to CFRP anchorage stress concentrations, highlighting the effective stress distribution and load-sharing synergy provided by CFRP-strengthening. Additionally, a numerical model based on the finite element (FE) method was developed using ABAQUS to simulate the component’s performance during the loading process. A comparison between the measured mid-span deflection of the strengthened slab and the numerically simulated values confirmed the high accuracy and rationality of the simulation method. Utilizing the validated numerical model, an analysis of the slab’s ultimate load capacity was conducted, demonstrating that the CFRP strengthening technique effectively increased the load-bearing capacity of the initially imperfect RC two-way slab by nearly 50%.